Risiko dan Perilaku terhadap Risiko Usaha Tembakau di Kabupaten Magelang: Risks and Risk-Related Behaviors in the Tobacco Business in Magelang Regency - Ihsannudin Ihsannudin (Fenomena, 2006)
Tobacco is a high-value economic commodity but carries substantial risks related to costs, production, prices, and income, particularly in tropical countries like Indonesia, where climate and price fluctuations are prevalent. This study aimed to measure the risk levels of tobacco farming in Temanggung and Muntilan and to analyze farmers' risk behavior. A survey was conducted using proportional random sampling of 50 farmers (20 from Temanggung, 30 from Muntilan) in Magelang Regency during the 2005 growing season. Risk was analyzed using the coefficient of variation, while farmers' risk behavior was assessed using a quadratic utility function model based on the Certainty Equivalent approach. The results showed that cost, production, price, and income risks were higher for Temanggung tobacco than for Muntilan tobacco, with coefficients of variation of 0.75, 0.90, 1.90, and -2.05 for Temanggung, and 0.40, 0.48, 0.30, and -0.55 for Muntilan, respectively. Despite all farmers incurring losses due to adverse weather, the majority exhibited risk-loving behavior (65% for Temanggung, 66.67% for Muntilan), followed by neutral and risk-averse attitudes. It is concluded that higher risks are not fully matched by proactive risk management. Recommendations include government intervention for price stabilization, risk guarantees, adequate capital readiness, and market information dissemination to prevent oversupply. Tembakau merupakan komoditas bernilai ekonomi tinggi namun memiliki risiko besar pada biaya, produksi, harga, dan pendapatan, terutama di daerah tropis seperti Indonesia yang rentan terhadap fluktuasi iklim dan harga. Penelitian ini bertujuan untuk mengukur tingkat risiko pada usaha tani tembakau jenis Temanggung dan Muntilan serta menganalisis perilaku petani dalam menghadapi risiko tersebut. Metode survei dilakukan dengan sampel proporsional random sebanyak 50 petani (20 Temanggung, 30 Muntilan) di Kabupaten Magelang pada musim tanam 2005. Analisis risiko menggunakan koefisien variasi, sementara perilaku petani terhadap risiko dianalisis dengan model fungsi utilitas kuadratik berdasarkan pendekatan Certainty Equivalent. Hasil penelitian menunjukkan bahwa risiko biaya, produksi, harga, dan pendapatan pada tembakau Temanggung lebih tinggi dibandingkan Muntilan, dengan koefisien variasi masing-masing 0,75; 0,90; 1,90; dan -2,05 untuk Temanggung, serta 0,40; 0,48; 0,30; dan -0,55 untuk Muntilan. Meskipun seluruh petani mengalami kerugian akibat cuaca buruk, mayoritas petani bersikap berani terhadap risiko (65% Temanggung, 66,67% Muntilan), diikuti netral dan menolak risiko. Disimpulkan bahwa risiko yang lebih tinggi tidak sepenuhnya diimbangi oleh perilaku berani petani. Disarankan adanya intervensi pemerintah dalam stabilisasi harga, jaminan risiko, peningkatan modal, serta informasi kebutuhan pasar untuk menghindari kelebihan pasokan.